STRATEGI PENCAPAIAN OPINI WTPPEMERINTAH KABUPATEN BONDOWOSO DALAM PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL - Setyawati, Heny (BISMA: Jurnal Bisnis dan Manajemen, 2017)
Abstract: New Public Management has reformed the financial management of the public sector by adopting approaches from the private sector in order to achieve organizational efficiency and effectiveness (including local and central government finances) and it was the reason behind the implementation of Accrual-based Government Accounting Standards (SAP). The Governmentof Bondowoso also implements accrual-based SAP policy. This study used a qualitative approach by using Strenghts Weaknessess Opportunities Threats (SWOT) analysis in the early stage to describe the strategy and then completed by in depth interview. The informants were 8 (eight) key persons in the Government of Bondowoso with significant roles in achieving the unqualified opinion in implementing the accrual-based SAP. Results show that commitment from the leaders of local government and institutions, financial statements presentation that in line with the SAP, sufficient internal control system, and the follow-up on the State Audit Agency’s recommendations on the local government financial statements are the major strengths in achieving the unqualified opinion of the accrual-based SAP. The opportunities in Strength-Opportunity (SO) strategy are the issuance of various laws and regulations and technical guidance of accrual-based accounting standards by the central government. Keywords: Unqualified Opinion, Accrual Based SAP, SWOT, Strategy.